School counselors and school psychologists as collaborators of college and career readiness for students in urban school settings. Issue 3 (12th August 2019) - Hines, Erik M.; Vega, Desiree D.; Mayes, Renae; Harris, Paul C.; Mack, Michelle
Abstract : Purpose: The purpose of this paper is to discuss the role of both the school counselor and the school psychologist in preparing students in urban school settings for college and/or the workforce. Throughout this paper, the authors discuss how collaboration is critical to ensuring students are successful at every school level (e.g., elementary, middle and high) to avail themselves of various postsecondary opportunities upon graduation. The authors give recommendations for practice and future research to implement and increase knowledge around collaboration between school counselors and school psychologists in preparing students in urban school settings to be college- and career-ready. Design/methodology/approach: This is a conceptual paper on school counselors and school psychologists using the Eight Components of College and Career Readiness Framework to collaborate on preparing students for postsecondary options. Findings: With support from key stakeholders like administrators, teachers and parents, school counselors and school psychologists can work collaboratively to increase students' college and career readiness. For example, school counselors and school psychologists may start by creating and implementing a needs assessment, as it relates to the developmental tasks of students (i.e. self-regulation, self-efficacy, self-competence) that must be negotiated to ensure college and career readiness. School counselors and school psychologists should also examine out-of-school suspension, expulsion, school arrest and disciplinary referral data (Carter et al., 2014 ). Originality/value: Collaboration around college and career readiness is important to the academic success and future of students in urban school settings. School counselors and school psychologists complement each other in preparing students for college and the workforce because their training has prepared both for addressing academic needs, assessment, mental health issues, career development, behavioral concerns and social–emotional needs of students (American School Counselor Association, 2012; National Association of School Psychologists, 2014). Further, school counselors and school psychologists are in a pivotal position to create a college-going culture by using evidence-based activities, curricula and practices.